Implementasi modul analisis konsentrasi protein terhadap hasil belajar dan respon mahasiswa pada pembelajaran biokimia II - Mellyta Uliyandari; Sumpono Sumpono; Agus Susanta (PendIPA Journal of Science Education, 2019)
AbstraCT [Implementation of  Module  Protein Concentration Analysis on Learning Outcomes and Student Response to Biochemical Learning II]. This study aims to look at the effect of the implementation of the use of the "Protein Concentration Analysis" module on student learning outcomes and responses to Biochemical II learning. This research is a type of research and development (Research and Development) which aims to investigate patterns and sequences of growth or change as a function of time. Based on the results of this study it is known that the average pretest score of students before using the module is 56.34 ± 11.65 with the lowest score of 33, and the highest score of 73, and the most scores obtained by students range from 60-69, while the average posttest results the average student after using the module is 84.68 ± 8.67, with the lowest score of 60, and the highest score of 100. Based on the learning outcomes that have been carried out it is known that the learning process using the module gives an increase in learning outcomes in Chemistry Education students VI Semester FKIP UNIB. The results of the questionnaire responses of students to learning activities using modules are in the good category which is at a score of 46.8, and the response of students to the modules used in learning is at a score of 19.2 with good categories. Keywords: Modules; Learning Outcomes; Student Response (Received July 29, 2019; Accepted September 18, 2019; Published October 8, 2019) Abstrak Penelitian ini bertujuan untuk melihat pengaruh implementasi penggunaan modul “Analisis Konsentrasi Protein”  terhadap hasil belajar dan respon mahasiswa pada pembelajaran Biokimia II. Penelitian ini termasuk jenis penelitian dan pengembangan (Research and Development) yang bertujuan untuk menyelidiki pola dan perurutan pertumbuhan atau perubahan sebagai fungsi waktu. Berdasarkan hasil penelitian ini diketahui bahwa nilai pretest rata-rata mahasiswa sebelum menggunakan modul adalah 56,34 ± 11,65 dengan skor terendah 33, dan skor tertinggi 73, dan nilai terbanyak yang diperoleh mahasiswa berkisar pada 60-69, sedangkan hasil posttest rata-rata mahasiswa setelah menggunakan modul yaitu 84,68 ± 8,67, dengan skor terendah 60, dan skor tertinggi 100. Berdasarkan hasil pembelajaran  yang telah dilakukan diketahui bahwa, proses pembelajaran dengan menggunakan modul memberikan peningkatan hasil belajar pada mahasiswa Pendidikan Kimia Semester VI FKIP UNIB. Hasil angket respon mahasiswa terhadap kegiatan pembelajaran menggunakan modul berada pada katagori baik yaitu berada pada skor 46,8, dan respon mahasiswa terhadap modul yang digunakan dalam pembelajaran  berada pada skor 19,2 dengan katagori baik. Kata Kunci : Modul; Hasil Belajar; Respon Mahasiswa